Preparation and Characterization of Polyurethane Foams from Bio-based Succinate Polyols - Tatcha Sonjui (Science Faculty of Chiang Mai University, 2019)
The goal of this work is to study the feasibility of using bio-based succinate polyol from succinic acid (SA) in preparation of bio-based polyurethane (PU) foams. Bio-based succinate polyols were synthesized by condensation reaction using SA and three types of glycols that are diethylene glycol (DEG), triethylene glycol (TEG) and tetraethylene glycol (TTEG) in the molar ratio of 1:2. Bio-based PU foams were prepared using the synthesized polyols with polymeric methylene diphenyl diisocyanate (PMDI) and H2O as blowing agent. The effects of chain length of prepared polyols toward physical properties of PU foams were studied. Physical and mechanical properties of the prepared PU foams were taken relatively to PU foam obtained from a commercial polyol. The results revealed that hydroxyl number (OH number) and viscosity of prepared polyols decreased as the length of the glycol chains increased (DEG < TEG < TTEG). Optical micrographs images showed that the PU foam prepared from DEG succinate polyol had smaller cell size compared to those prepared from TEG and TTEG succinate polyol respectively. Foam formation time and compressive strength of foams prepared from DEG succinate polyol showed similar results as ones prepared from commercial polyol (POLIMAXX A8360).